Hybrid HCS-fuzzy mppt algorithm for hydrokinetic energy harnessing - Wan Ismail, Ibrahim; Mohd Rusllim, Mohamed; Raja Mohd Taufika, Raja Ismail (Institute of Electrical and Electronics Engineers Inc., 2022)
This paper proposes a hybrid maximum power point tracking (MPPT) algorithm for the stand-alone hydrokinetic technology in river application. The fixed stepsize Hill Climbing Search (HCS) algorithm is widely used due to its simplicity. However, the operating point oscillates around the maximum power point (MPP) during dynamic steady-state resulting waste some amount of energy. The proposed algorithm is the combination of the Fuzzy Logic Controller (FLC) and HCS algorithm to provide the variable step-size to eradicate the limitation of conventional HCS algorithm. The proposed algorithm has been compared with the Small Step HCS (SS-HCS) to investigate the performance of the algorithm. The simulation results illustrated the proposed algorithm (Fuzzy-HCS) improved the output power with 89.91 % efficiency and minimizes oscillation during dynamic steady-state.